2008
DOI: 10.1111/j.1526-100x.2008.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Target Map of Native Species Assemblages for Restoration

Abstract: Vegetation restoration is usually based on predefined species assemblages from large-scale maps of potential vegetation. However, most restoration plans apply to smaller spatial scales, so a homogeneous species assemblage is usually assigned to the target site. We propose defining species assemblages for restoration by modeling the distribution of individual target species. The example presented here is about postfire restoration, but it can be used in other types of disturbed areas. We surveyed 212 plots in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In our case, it appeared that potential natural vegetation could be used as an effective tool for predicting general trends of succession (see also Siles et al. ; Somodi et al. ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our case, it appeared that potential natural vegetation could be used as an effective tool for predicting general trends of succession (see also Siles et al. ; Somodi et al. ).…”
Section: Discussionmentioning
confidence: 56%
“…We can, however, reasonably expect the changes to be much smaller than the differences between seral and potential vegetation. In our case, it appeared that potential natural vegetation could be used as an effective tool for predicting general trends of succession (see also Siles et al 2010;Somodi et al 2012). We do not claim all the successions studied definitely approach potential vegetation or that the process is linear over the course of succession.…”
Section: Discussionmentioning
confidence: 68%
“…Siles et al . () modelled the recovery of vegetation after a fire in Pinus nigra , Quercus ilex and Q. faginea forest in south‐east Spain and found that the presence of S. torminalis was associated with a southerly aspect, shallow soils and a high rock cover (as were other species tolerant of dry conditions), although altitude and slope were not important. Slope angle only seems to become important on the wettest soils when S. torminalis is restricted to the drier, steeper slopes (Wohlgemuth ).…”
Section: Habitatmentioning
confidence: 99%
“…The requirement for warm and dry conditions tends to restrict S. torminalis to south-facing slopes, particularly at the northern and eastern edge of its range (Dinca 2000) although towards the south edge of its range, it occurs primarily on cooler, damper north facing slopes (De Dominicis & Barluzzi 1983). Siles et al (2010) modelled the recovery of vegetation after a fire in Pinus nigra, Quercus ilex and Q. faginea forest in south-east Spain and found that the presence of S. torminalis was associated with a southerly aspect, shallow soils and a high rock cover (as were other species tolerant of dry conditions), although altitude and slope were not important. Slope angle only seems to become important on the wettest soils when S. torminalis is restricted to the drier, steeper slopes (Wohlgemuth 1993).…”
Section: Habitat ( a ) C L I M A T I C A N D T O P O G R A P H I mentioning
confidence: 99%
“…In these plots, naturally regenerating pioneer vegetation was eliminated using a string trimmer. Subsequently, we planted 60 seedlings of different tree species in each plot, with species distributed according to the characteristics of each zone (Siles et al. 2009).…”
mentioning
confidence: 99%